Assessing knowledge, attitude, and practice of adaptive designs in clinical trials among Indian stakeholders - Aithal, Yashoda; Eldhose, Merin; Shetty, Yashashri; Sinha, Soham; Gite, Rucha (International Journal of Research in Medical Sciences, 2025)
Background: This study attempted to evaluate the knowledge, attitude and practices of various stakeholders addressing adaptive clinical trials (ACT), as no analogous studies have been published in India. Methods: Ethics committee (EC) approval was sought before circulating an online pre-validated questionnaire (28 questions in three domains) among 200 stakeholders involving the clinicians, clinical trial unit personnel, and medical advisors from various pharmaceutical industries. The responses collected were analysed using appropriate statistical tests. A p value <0.05 was considered significant. Results: Out of the 200 participants surveyed, 169 responded, yielding a response rate of 84.5%. When the three distinct stakeholders’ median knowledge scores were evaluated, there was no statistically significant difference. The median knowledge score of stakeholders with more than five years of experience did not vary statistically from those with less than five years. In the attitude domain, 21.8% and 17.1% of participants agreed that the validity and integrity of research in ACT are hampered respectively. However, 73.9% felt that ACT has potential benefits while 79.2% believed they were underutilized. In the practice domain, only 4.7% of stakeholders have been a part of adaptive clinical trials. Conclusions: The study found that fewer stakeholders participated in studies utilizing adaptive designs, which resulted in a decrease in knowledge, perception, and practices among the various stakeholders. This emphasizes the necessity for further educational initiatives in the future, such as planning conferences or training sessions, to raise the understanding of adaptable designs in clinical trials.